ALTERNATIVE METHOD OF THE ACTIVATION PROCESS FOR BENTONITE MINERAL - DESSY AMALIA; MUCHTAR AZIZ; STEFANUS S. CAHYONO (Indonesian Mining Journal, 2010)
Biodiesel manufacture usually applies liquid catalyst (homogenic catalyst) that deals with some obstacles, such as difficulty in catalyst product separation as they are in the same liquid phase, corrosive characters, excessive catalyst cannot be reused, and complicated to be handled. An alternative for a better process is solid catalyst as a heterogeneous system between raw material and product. Bentonite has layer structures and a potential to be used as solid catalyst by activation process. Three methods of activation process had been conducted,namely 60°C-heating; 60°C-heating followed by 1 week settling and 2 weeks settlement. Each method was performed in sulphuric acid and the chemical content of Al2O3 and SiO2 was observed. An activated bentonite has a molar ratio of SiO2 and Al2O3 between 6 - 9. All methods resulted in expected molar ratio, but the 2 weeks settlement process without heating provided more significant result which means it performed energy saving compared to other methods.